Telemental health services during COVID-19 outbreak in Saudi Arabia - Ruddin, Fajar; Saeed Alzahrani, Sami (Asian Journal of Islamic Psychology, 2024)
COVID-19, which was declared a pandemic by WHO, brings up many problems. Telemental health comes as a solution to mental problems that are difficult to deal with because of social and physical distancing policies. This study aims to describe the telemental health services in Saudi Arabia during the COVID-19 outbreak. This paper outlines the general approach Saudi Arabia has taken in delivering public mental health services. It describes several key areas of work: medical staff, COVID-19 patients and their families, and individuals who feel anxious due to COVID-19. A description of the program that Saudi Arabia has produced is described, which targeted various groups with various methods. The program from Saudi Arabia may assist in informing public mental health services during COVID-19 or other crises that other government agencies could consider adopting. There is limited published information on this topic in Saudi Arabia. This paper gives a piece of detailed information on mental health services during the COVID-19 outbreak.